2002
DOI: 10.1051/0004-6361:20020388
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and kinematics in the central broad-line region of a Seyfert 1 galaxy

Abstract: Abstract.We recorded spectra of the highly variable Seyfert 1 galaxy Mrk 110 in a variability campaign with the 9.2 m Hobby-Eberly Telescope at McDonald Observatory in order to study the detailed line profile variations of the broad emission lines. Here we show that only an AGN model predicting the formation of the broad Hβ line emission in the wind of an accretion disk matches the observed 2-D variability pattern. Furthermore, we derive an improved mass of the central supermassive black hole of M = 1.07 M fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
6

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 20 publications
3
31
0
6
Order By: Relevance
“…It is intriguing that the very broad-line AGN 3C 390.3 shows the same pattern in the velocity-delay maps as the narrow-line AGN Mrk 110 (see Kollatschny & Bischoff 2002;Kollatschny 2003). The outer red and blue wings respond much faster to continuum variations than the central regions.…”
Section: D Ccf Of the Hβ Line Profilesmentioning
confidence: 85%
See 1 more Smart Citation
“…It is intriguing that the very broad-line AGN 3C 390.3 shows the same pattern in the velocity-delay maps as the narrow-line AGN Mrk 110 (see Kollatschny & Bischoff 2002;Kollatschny 2003). The outer red and blue wings respond much faster to continuum variations than the central regions.…”
Section: D Ccf Of the Hβ Line Profilesmentioning
confidence: 85%
“…We proceed in the same way as for the line-profile variations in Mrk 110 (Kollatschny & Bischoff 2002;Kollatschny 2003). Figure 14 shows the maximum response of the correlation functions of the Hβ line segment light curves with the continuum light curve, and Fig.…”
Section: D Ccf Of the Hβ Line Profilesmentioning
confidence: 99%
“…The line widths of Mrk 926 amount to 10 000 km s −1 (FWHM) compared to line widths of 2000 km s −1 only in Mrk 110 (Kollatschny et al 2001). It has been demonstrated that the narrow Balmer and helium emission lines in Mrk 110 originate in an accretion disk seen nearly face on (Kollatschny 2002(Kollatschny , 2003. The response of the very broad emission lines in Mrk 926 might be caused by an accretion disk seen nearly edge on relative to e.g.…”
Section: D Velocity Mapmentioning
confidence: 98%
“…We proceed in the same way as when we studied the line profile variations in Mrk 110 (Kollatschny & Bischoff 2002;Kollatschny 2003).…”
Section: -D Ccf Of the Hα And Hβ Line Profilesmentioning
confidence: 99%
See 1 more Smart Citation